PHYLOGENETIC DIVERSITY OF SECONDARY METABOLITE PRODUCING-BACTERIA ASSOCIATED WITH SPONGES FROM BANDENGAN WATERS, JEPARA - Ocky Karna Radjasa; Agus Sabdono (JOURNAL OF COASTAL DEVELOPMENT, 2006)
A total of 13 bacterial isolates associated with sponges collected from Bandengan water, Jepara, North Java Sea, Indonesia, was successfully screened for antibacterial activity against pathogenic bacteria Vibrio parahaemolyticus, Aeromonas hydrophila  and Staphylococcus aureus. Active bacterial isolates were rapidly grouped by using rep-PCR and a dendrogram was constructed. Six isolates were further selected based on the constructed dendrogram for subsequent DNA sequencings, resulted in the richness of secondary metabolite-producing bacteria associated with sponges from Bandengan having closest similarity to Pseudoalteromonas, Brachybacterium, Vibrio, alpha proteobacterium and uncultured bacterium clones.